Factor structure of the Communicator Styles Measure (CSM) when used with undergraduate health science students. Issue 2 (30th July 2012) - Brown, Ted; Boyle, Malcolm; Williams, Brett; Molloy, Andrew; McKenna, Lisa; Palermo, Claire; Molloy, Liz
<x xml:space="preserve">Abstract</x> Scand J Caring Sci; 2013; 27; 363–372 Factor structure of the Communicator Styles Measure (CSM) when used with undergraduate health science students Background: It is important for educators to consider the communication skills of students enrolled in health science programmes. To date, research into this area is limited, and having measures that are valid and reliable would assist educators and researchers to complete high‐quality investigations. Purpose: The purpose of this study was to investigate the factor structure of Communicator Styles Measure. Method: Data from the Communicator Styles Measure completed by 860 undergraduate health science students enrolled in eight different courses at an Australian university (response rate of 59%) were analysed using principal component analysis with varimax rotation and a cluster analysis using elementary linkage analysis. The Communicator Styles Measure is a self‐report scale consisting of 40 items designed to assess ten communication styles and one's perception of his/her ability to communicate. Results: Communicator Styles Measure items loaded onto five new viable factors labelled personable, energetic, confident, open and confronting. Six items of the original 40 from the Communicator Styles Measure did not load onto any factor and were therefore considered redundant. Conclusion: The original factor structure proposed by the Communicator Styles Measure's author was not supported, which calls into question its construct validity. However, the five new factors identified in this study may be useful for researchers and educators when assessing the communication skills of students and practitioners. Further investigation into the construct validity and reliability of the five new Communicator Styles Measure factors is recommended.